UJI TOKSISITAS ANTIKANKER DAUN BELUNTAS (Plucea indica) - Aktsar Roskiana Ahmad (As-Syifaa Jurnal Farmasi, 2009)
ToxicityTest anticancer of Beluntas Folium (Plucea indica).  The research was mainly to give information of  anticancer activity of beluntas. Takeing sample in in Makassar city  with interview  public figure. Toxicity test with Brine Shrimp Lethality Test (BST) method and used negatif control sea water. The result, beluntas haven anticancer activity and LC50 is 44,31 ±  12,65 mg/ml.Keyword : Anticancer, Plucea indica